2015
DOI: 10.1007/s11845-015-1359-5
|View full text |Cite
|
Sign up to set email alerts
|

GP supply, deprivation and emergency admission to hospital for COPD and diabetes complications in counties across Ireland: an exploratory analysis

Abstract: Geographical variation in rates of admission to hospital for chronic disease is associated with both population need and health system factors. These findings suggest that primary care resourcing must be a key consideration in any efforts to tackle acute hospital capacity problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Deprivation has been found to play a significant role in explaining the variation in standardised illness ratios13 and hospital admission rates 4 5 43. In the UK study, employment deprivation was found to account for 72% of the variation in potentially avoidable emergency admissions 5…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Deprivation has been found to play a significant role in explaining the variation in standardised illness ratios13 and hospital admission rates 4 5 43. In the UK study, employment deprivation was found to account for 72% of the variation in potentially avoidable emergency admissions 5…”
Section: Discussionmentioning
confidence: 99%
“…Two principal studies were identified as the most appropriate for considering drivers of potentially avoidable emergency admissions in Ireland, one based in Ireland4 and one in the UK 5. A priori factors were chosen from these studies and other literature, and adapted for the Irish context (see table 1 and online supplementary appendix 2 for factor construction).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations